Melatonin Alleviates Oxidative Stress Induced by H2O2 in Porcine Trophectoderm Cells - Yawei Fu; Yue Chen; Zhao Jin; Hu Gao; Gang Song; Qian Wang; Kang Xu (MDPI AG, 2022)
Placental oxidative stress has been implicated as a main risk factor for placental dysfunction. Alleviation of oxidative stress and enhancement of antioxidant capacity of porcine trophectoderm (PTr2) cells are effective means to maintaining normal placental function. The present study was conducted to evaluate the protective effect of melatonin (MT) on H2O2-induced oxidative damage in PTr2 cells. Our data revealed that pretreatment with MT could significantly improve the decrease in cell viability induced by H2O2, and reduce intracellular reactive oxygen species (ROS) levels and the ratio of apoptotic cells. Here, we compared the transcriptomes of untreated versus melatonin-treated PTr2 cells by RNA-seq analysis and found that differentially expressed genes (DEGs) were highly enriched in the Wnt signaling, TGF-beta signaling and mTOR signaling pathways. Moreover, pretreatment with MT upregulated the antioxidant-related genes such as early growth response3 (EGR3), WAP four-disulfide core domain1 (WFDC1), heme oxygenase1 (HMOX1) and vimentin (VIM). These findings reveal that melatonin protects PTr2 cells from H2O2-induced oxidative stress damage.